Pedagogical Content Knowledge of Elementary Math Teachers (International Conference on Elementary Education, 2018)
The purpose of this qualitative case study is to get an in-depth understanding of how 13 grade 5 elementary school mathematics teachers in professional learning communities demonstrate their pedagogical content knowledge. Data collection uses triangulation techniques, namely document study, observation, and interview. The results showed that by learning in professional learning community teachers would assist in lesson plan, carrying out learning activities, and assessment so that they could improve their pedagogical content knowledge. It was also revealed that the practice of teaching math in class was in line with the learning plans they had prepared in advance. Based on the implementation of professional teacher learning activities it can be concluded that the knowledge and skills of teachers in teaching mathematics are well developed, develop the curriculum, and can better master the characteristics of students.